An Investigation of Healthcare Worker Perception of Their Workplace Safety and Incidence of Injury. (May 2020) - Aljabri, Duaa; Vaughn, Andrew; Austin, Matthew; White, Launia; Li, Zhuo; Naessens, James; Spaulding, Aaron
Background: Managing the safety climate in health care is a promising tool for improving employee and patient safety in the health care work environment. Gaps in the theoretical and conceptual underpinnings of safety climate, as well as the evidence base for its practical application in health care remain. The purpose of this study was to evaluate the number of work injuries occurring in health care work units and associated safety climate beliefs. Methods : A retrospective analysis was conducted utilizing organizational staff survey data collected by a large medical hospital in the Midwest in 2015. Employees ( n = 32, 327) were invited to identify safety climate perceptions via survey. Injuries, days restricted, and days absent were identified through the Hospital's Occupational Safety and Health Administration (OSHA) log. Zero inflated negative binomial regressions used injuries as dependent variables and safety climate perceptions as independent variables. Findings : In all, 23, 599 employees completed the survey (73% response rate) across 1, 805 employee work units which were defined as groupings of employees reporting to a single supervisor. We found that there was an association between fewer injuries and health care workers indicating that they share responsibility for compliance with safety rules and procedures (relative risk [RR] = 0.98, 95% confidence interval [CI] = [0.98, 0.99]). Conclusion/Application to Practice : This study supports the use of a safety climate measure to assess working units' perceptions of employee safety. A continued focus on the health and safety of employees who interact directly with patients is warranted, as well as employees who do not provide direct patient care.